Meningkatkan Hasil Belajar Pendidikan Agama Katolik Melalui Model PBL pada Siswa SD Negeri Jagalan Surakarta - Kristin Sulistyowati (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to determine the increase in cognitive and affective learning outcomes in the dimensions of personal and creative morals through the PBL model for students at Jagalan State Elementary School, Surakarta. This type of research is classroom action research with research steps namely planning, implementation, observation and reflection in each cycle. This research consists of two cycles. The research location was at Jagalan Surakarta State Elementary School for class IV students with material on the Ten Commandments of God as a Guide to Life. The research was carried out in September 2024. Data collection techniques used learning outcomes tests and affective observation rubrics. The data analysis technique uses quantitative descriptive techniques. From the research results, there was an increase in cognitive learning outcomes of 27.5% in the Proficient criteria and 12.5% ​​in the Capable criteria. Affective learning outcomes using the PBL learning model have been proven to improve the affective learning outcomes of students at Jagalan Surakarta State Elementary School on the Ten Commandments of Allah as a Guide to Life. The results of the increase can be seen from the number of students in cycle I who were 100% in the Eligible criteria and in cycle II there was a significant change, namely 67.5% were in the proficient criteria and 37.5% were in the proficient criteria.